Risk factors for adverse outcome in asphyxiated new born in Eastern Nepal - Yadav, Satish; Shah, Gauri Shankar; Poudel, Prakash; Mishra, Om Prakash (International Journal Of Community Medicine And Public Health, 2017)
Background: Birth asphyxia is the third leading cause of neonatal deaths in developing countries. The present study was an attempt to find out the various risk factors associated with mortality in these cases. Methods: This was a retrospective hospital based analysis of data in neonates with birth asphyxia admitted during the period February 2010 to January 2011. The demographic profile and outcome were recorded. Results: Of 285 neonates, there were 212 (74.4%) outborn and 73 (25.6%) cases were inborn. Male were 207 (72.6%) and female were 78 (27.4%). One hundred eighty eight (66%) came from rural area. Two hundred sixty six (93.3%) were full term and 19 (6.7%) were preterm. Thirty two (11.2%) were delivered at home and 253 (88.8%) were institutional delivery among which 54 (18.9%) babies were born by caesarean section while 215 (75.4%) were by normal vaginal delivery and 16 (5.6%).were instrumental delivery. Thirty eight (13.3%) were found to be normal while clinical signs of HIE were present in 247(86.7%) babies, out of those 48 (16.8%) babies were in stage I, 136 (47.7%) in Stage II and 63 (22.1%) in stage III of HIE. Fifty nine (20.7%) babies died during the hospital stay. The babies who were born at home (p=0.028, OR=2.472, 95% CI 1.104-5.536), prematurity (p=0.024, OR=3.154, 95% CI 1.166-8.528) and shock at the time of admission (p=0.035, OR=2.261, 95% CI 1.061-4.821) had higher risk of mortality. Conclusions: Thus unsupervised delivery at home, prematurity and presence of shock at admission affected the outcome in these babies. Therefore, institutional delivery with facility to care preterm baby and immediate treatment of complications are needed for better survival.